Study of Neurodevelopmental Outcomes at 10-14 Months of Age Using Bayley Scale of Infant and Toddler Development in Asphyxiated Newborns with Hypoxic Ischemic Encephalopathy Treated with and without Therapeutic Hypothermia - Jayashree Purkayastha; Maitreyee Dutta; Leslie Edward Lewis; Ramesh Bhat Y; Joshua Rajan X; Gaurav Ayappa (Mashhad University of Medical Sciences, 2018)
Background: Therapeutic hypothermia has become an established protocol for all neonates with moderate to severe Hypoxic Ischaemic Encephalopathy (HIE). There are very few studies comparing the neurodevelopmental outcomes in asphyxiated neonates who received therapeutic hypothermia or did not. This study aimed to assess the neurodevelopmental outcomes of asphyxiated neonates with features of HIE at 10-14 months of age using Bayley Scale of Infant and Toddler Development III (BSID III) and to compare this outcome between neonates who received therapeutic hypothermia and those who did not. Methods: Term infants with HIE admitted in neonatal intensive care unit (NICU) at a tertiary referral hospital were followed up at 10-14 months of age from December 2013 to August 2015. Neurodevelopmental outcomes were assessed using BSID III. Results: A total of 76 neonates with birth asphyxia were admitted to NICU between December 2012 and August 2014. These neonates were followed up from December 2013 to August 2015, and 34 of them were included in the study. At10-14 months of age, 8 neonates (23.5%) had cognitive delay, 14 cases (41.17%) had motor delay, and 9 newborns (26.4%) had language delay using BSID III score of < 85 as cut off. Twenty (58.82%) infants had normal development in all 3 domains. Higher percentage of infants (73.68%) who received therapeutic hypothermia had normal BSID Score  as compared to 40% of the neonates with normal BSID score (>85) who did not receive therapeutic hypothermia. Statistical analysis using Chi-square test showed P-value of 0.048 as statistically significant. Conclusion: Neurodevelopment assessment at 10-14 months of age using BSID III of asphyxiated neonates with HIE showed significantly better outcome in infants who received therapeutic hypothermia than those who did not.